Catalyst with noble metal element loaded on oxide carrier, preparation method and reactor

By loading the catalyst of precious metal elements on the oxide support, CO-SCR technology is used to solve the problem of removing NOx and CO in the flue gas of steel plants, and a catalytic effect with high efficiency and long life is achieved.

CN119771401APending Publication Date: 2025-04-08TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510001112.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

There are a large amount of NOx and CO in the industrial flue gas of steel plants, and the competition for oxygen adsorption leads to oxidation of the active sites of the catalyst, resulting in the deactivation of the catalyst, making it difficult to effectively remove these harmful gases.

Method used

The catalyst supported by precious metal elements (such as Ir) is used to reduce NOx by reducing NOx through selective catalytic reduction technology (SCR) to alleviate the problem of oxygen competition adsorption.

Benefits of technology

It improves the removal effect of nitrogen oxides and carbon monoxide, extends the service life of the catalyst, and can still efficiently remove CO and NOx under high oxygen concentrations.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119771401A_ABST
    Figure CN119771401A_ABST
Patent Text Reader

Abstract

The invention discloses a catalyst with noble metal elements loaded on an oxide carrier, a preparation method and a reactor. The catalyst comprises an oxide carrier and a noble metal element loaded on the oxide carrier, the noble metal element is selected from at least one element of Au, Ag, Ru, Rh, Pd, Os, Ir and Pt, the general formula of the oxide carrier is SiMOx, M is an additive element, the additive element M is selected from at least one element of Ce, La, Pr and Zr, and x is greater than or equal to 1. X is the number of O atoms required by valence balance of the general formula. According to the catalyst disclosed by the invention, the noble metal is dispersed in the oxide carrier, so that the removal effect on nitrogen oxides and carbon monoxide can be effectively improved. The invention is suitable for the occasion of harmful gas denitration.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of harmful gas treatment, and in particular to a catalyst in which a noble metal element is loaded on an oxide carrier, a preparation method and a reactor. Background Art

[0002] At present, there are a large number of toxic and harmful gases such as NOx, CO, SO2 in automobile exhaust and industrial flue gas from steel mills, especially in industrial flue gas from steel mills. Nitrogen oxides (NOx) are inevitable global air pollutants that can cause environmental problems such as photochemical smog, acid rain and ozone layer depletion. CO itself is a reducing atmosphere. Using CO to reduce NOx can not only effectively remove NOx and CO at the same time, but also greatly reduce the subsequent flue gas treatment costs. CO in the flue gas is oxidized to CO2, and NO is reduced to harmless N2, achieving "waste treatment with waste", which is a green and low-energy denitrification technology. However, due to the large amount of oxygen in the flue gas from steel mills, this will lead to competitive adsorption on the catalyst surface and even oxidation of the active sites of the catalyst, resulting in catalyst deactivation. Summary of the invention

[0003] In view of this, the present invention provides a catalyst, a preparation method and a reactor in which a precious metal element is loaded on an oxide carrier, which can effectively improve the removal effect of nitrogen oxides and carbon monoxide.

[0004] In order to achieve the above object, the present invention adopts the following technical solutions: In a first aspect, the present invention provides a catalyst in which a precious metal element is loaded on an oxide carrier, the catalyst comprising an oxide carrier, and a precious metal element loaded on the oxide carrier, the precious metal element being selected from at least one element of Au, Ag, Ru, Rh, Pd, Os, Ir, and Pt, and the general formula of the oxide carrier being SiMOx, wherein M is an additive element, the additive element M being selected from at least one element of Ce, La, Pr, and Zr, and x being the number of O atoms required to satisfy the valence balance of the general formula.

[0005] In a specific embodiment, the noble metal element is Ir, the additional element M is Ce, and the oxide support is a mixed oxide containing SiO2 and CeO2.

[0006] In a second aspect, the present invention provides a method for preparing a catalyst in which a noble metal element is supported on an oxide carrier, comprising the following steps: Step S1, dissolving citric acid in a mixed solution of deionized water and ethanol, adding an additive element M precursor and a Si precursor, stirring until completely dissolved, then adding polyethylene glycol, heating and stirring to obtain a gel, wherein the additive element M is at least one element selected from Ce, La, Pr, and Zr; Step S2, drying the gel and then calcining it in air to obtain an intermediate; Step S3, dispersing the intermediate in deionized water, adding an aqueous solution containing a precious metal element, heating and stirring until evaporated to dryness, drying, and air calcining to obtain a catalyst in which the precious metal element is supported on an oxide carrier, wherein the precious metal element is selected from at least one element of Au, Ag, Ru, Rh, Pd, Os, Ir, and Pt.

[0007] In a specific embodiment, in step S1, the ratio of the sum of the moles of the additive element M precursor and the Si precursor, the moles of polyethylene glycol, the moles of deionized water, and the moles of ethanol is 30:0.3:222:121.

[0008] In a specific embodiment, in step S1, the molar ratio of citric acid to the precursor of the additive element M is 1:1.

[0009] In a specific embodiment, in the step S1, the molar ratio of the Si precursor to the additive element M precursor is 1:(0.2-5).

[0010] In a specific embodiment, in step S3, the mass ratio of the intermediate to deionized water is 1:50; the mass ratio of the noble metal element in the aqueous solution containing the noble metal element to the intermediate is 0.1%-5%, and the concentration of the aqueous solution containing the noble metal element is 1 mg / ml.

[0011] In a specific embodiment, in step S1, the temperature of heating and stirring is 80°C; and / or In the step S2, the drying temperature of the gel is 100°C and the drying time is 12 hours; the air calcination temperature of the gel is 550°C and the air calcination time is 1 hour; and / or In the step S3, the heating and stirring time is 2 hours, the heating and stirring temperature is 80°C; the drying temperature is 100°C; the air calcination temperature is 550°C, and the air calcination time is 1 hour.

[0012] In a specific embodiment, the additional element M is Ce, and / or the noble metal element is Ir.

[0013] In a third aspect, the present invention further provides a reactor, comprising a catalyst for promoting a chemical reaction between nitrogen oxides and carbon monoxide, wherein the catalyst is any of the catalysts provided in the embodiments of the present application.

[0014] The present invention provides a catalyst in which a noble metal element is loaded on an oxide carrier, a preparation method and a reactor. The catalyst comprises an oxide carrier and a noble metal element loaded on the oxide carrier, wherein the noble metal element is selected from at least one element of Au, Ag, Ru, Rh, Pd, Os, Ir and Pt, and the general formula of the oxide carrier is SiMOx, wherein M is an additive element, and the additive element M is selected from at least one element of Ce, La, Pr and Zr, and x is the number of O atoms required to satisfy the valence balance of the general formula. The catalyst can effectively improve the removal effect of nitrogen oxides and carbon monoxide. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0016] Figure 1 A flow chart of the method for preparing the catalyst provided by the present invention; Figure 2 The stability curve of the catalyst provided by the present invention. DETAILED DESCRIPTION

[0017] The embodiments of the present application are described in detail below with reference to the accompanying drawings.

[0018] It should be clear that the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.

[0019] There are a lot of toxic and harmful gases such as NOx, CO, SO2 in automobile exhaust and industrial flue gas of steel plants, especially in industrial flue gas of steel plants. Nitrogen oxides (NOx) are inevitable global air pollutants that can cause environmental problems such as photochemical smog, acid rain and ozone layer depletion. In order to improve the removal effect of nitrogen oxides and carbon monoxide, in the first aspect, the present invention provides a catalyst in which a precious metal element is loaded on an oxide carrier. The catalyst comprises an oxide carrier and a precious metal element loaded on the oxide carrier. The precious metal element is selected from at least one element of Au, Ag, Ru, Rh, Pd, Os, Ir, and Pt. The general formula of the oxide carrier is SiMOx, wherein M is an additive element, and the additive element M is selected from at least one element of Ce, La, Pr, and Zr. x is the number of O atoms required to satisfy the valence balance of the general formula.

[0020] The catalyst of the present invention, also called CO-SCR catalyst, is based on the selective catalytic reduction technology (Selective Catalytic Reduction, SCR), using carbon monoxide CO as a reducing agent to reduce NOx to N2. CO, as a reducing gas, is widely present in sintering and coking flue gas and motor vehicle exhaust. CO is also a colorless and odorless toxic gas. When the CO in the air exceeds 0.1%, it may cause human poisoning. Using CO to catalytically reduce NOx can not only reduce pollution control costs, but also eliminate NO and CO in flue gas, achieving waste treatment with waste.

[0021] In this embodiment, since the noble metal is dispersed on the surface of the oxide carrier by water bath impregnation, the catalyst has a high metal dispersion and redox ability, which can greatly increase the active sites of the catalyst and improve the catalytic activity of the catalyst. Moreover, the sintering and agglomeration of the noble metal is reduced to a certain extent, which improves the service life and catalytic activity of the catalyst as a whole. The catalyst of the present invention has high catalytic activity and nitrogen selectivity within the operating temperature range of 250°C to 300°C.

[0022] Optionally, in a specific embodiment, the noble metal element is Ir, the added element M is Ce, and the oxide carrier is a mixed oxide containing SiO2 and CeO2.

[0023] It should be further explained that different types of rare earth metals are added to the SiO2 carrier by the sol-gel method: Ce, La, Pr, Zr, and Ce is preferably selected as the added element. CeO2 has excellent ability to store and release oxygen, which makes the catalyst have stronger redox properties, and the abundant oxygen vacancies in CeO2 are more conducive to capturing precious metals, making the active component precious metals on the surface more dispersed. Finally, CeO2 has the ability to activate and convert oxygen in O2, and can protect the active component precious metals by consuming O2 in the gas to prevent them from being oxidized. In summary, the CO-SCR catalyst prepared by selecting Ce as the carrier component has better catalytic activity.

[0024] The present invention provides a catalyst in which a noble metal element is loaded on an oxide carrier. The catalyst comprises an oxide carrier and a noble metal element loaded on the oxide carrier, wherein the noble metal element is selected from at least one element of Au, Ag, Ru, Rh, Pd, Os, Ir and Pt, and the general formula of the oxide carrier is SiMOx, wherein M is an additive element, and the additive element M is selected from at least one element of Ce, La, Pr and Zr, and x is the number of O atoms required to satisfy the valence balance of the general formula, and the removal effect of nitrogen oxides and carbon monoxide can be effectively improved.

[0025] Second, as Figure 1 As shown, the present invention provides a method for preparing a catalyst in which a noble metal element is supported on an oxide carrier, which may include the following steps: Step S1, dissolving citric acid in a mixed solution of deionized water and ethanol, adding an additive element M precursor and a Si precursor, stirring until completely dissolved, then adding polyethylene glycol, heating and stirring to obtain a gel, wherein the additive element M is at least one element selected from Ce, La, Pr, and Zr; The sol-gel method is to uniformly mix compounds containing highly chemically active components in the liquid phase, and carry out hydrolysis and condensation chemical reactions to form a stable transparent sol system in the solution. After aging, the sol particles slowly polymerize to form a gel with a three-dimensional network structure. The gel network is filled with a solvent that has lost its fluidity to form a gel. Since the raw materials used are first dispersed in the solvent to form a low-viscosity solution, molecular-level uniformity can be obtained in a very short time. When forming the gel, the reactants are uniformly mixed at the molecular level. Therefore, some trace elements can be uniformly and quantitatively incorporated to achieve uniform doping at the molecular level. At the same time, the chemical reaction of the sol-gel method is easier to carry out and only requires a lower synthesis temperature. The diffusion of components in the sol-gel system is in the nanometer range.

[0026] Step S2, drying the gel and then calcining it in air to obtain an intermediate.

[0027] There are a large number of micropores in the gel, and a lot of gas and organic matter will escape during the air calcination process, causing shrinkage, which will affect the progress of air calcination. Therefore, it is necessary to dry it before air calcination to eliminate this effect.

[0028] Step S3, dispersing the intermediate in deionized water, adding an aqueous solution containing a precious metal element, heating and stirring until evaporated to dryness, drying, and air calcining to obtain a catalyst in which the precious metal element is supported on an oxide carrier, wherein the precious metal element is selected from at least one element of Au, Ag, Ru, Rh, Pd, Os, Ir, and Pt.

[0029] In the liquid phase, the chemical reaction of the reaction compounds is easier to carry out, and the diffusion of the components can be made within the nanometer range. In addition, the catalyst provided by the present invention selects precious metals as active components, which can effectively alleviate the competitive adsorption problem of oxygen, NOx and CO, and synergistically remove CO and NOx at a lower temperature. In the oxide carrier of the present invention, SiOx plays a role in dispersing the added element M, so that the MOx in the carrier is evenly distributed on the surface and inside. Due to the strong interaction between the precious metal and the added element M, MOx acts as a capture site for the active precious metal during the impregnation process, and the two are closely combined, which indirectly improves the dispersion of the precious metal. The electron transfer between the precious metal and the added element M enables the precious metal to remain in a reduced state to the greatest extent, effectively alleviating the problem of the active site of the oxygen oxidation catalyst.

[0030] Optionally, in a specific embodiment, in step S1, the ratio of the sum of the moles of the element M precursor and the Si precursor, the moles of polyethylene glycol, the moles of deionized water, and the moles of ethanol is 30:0.3:222:121.

[0031] Optionally, in a specific embodiment, in step S1, the molar ratio of citric acid to the precursor of the added element M is 1:1.

[0032] Optionally, in a specific embodiment, in step S1, the molar ratio of the Si precursor to the added element M precursor is 1:(0.2-5).

[0033] Optionally, in a specific embodiment, in step S3, the mass ratio of the intermediate to deionized water is 1:50; the mass ratio of the noble metal element in the aqueous solution containing the noble metal element to the intermediate is 0.1%-5%, and the concentration of the aqueous solution containing the noble metal element is 1 mg / ml.

[0034] Optionally, in a specific embodiment, in step S1, the temperature for heating and stirring is 80°C; and / or in step S2, the drying temperature of the gel is 100°C, and the drying time is 12 hours; the temperature for air calcination of the gel is 550°C, and the air calcination time is 1 hour; and / or in step S3, the time for heating and stirring is 2 hours, the temperature for heating and stirring is 80°C; the drying temperature is 100°C; the air calcination temperature is 550°C, and the air calcination time is 1 hour.

[0035] Optionally, in a specific embodiment, the added element M is Ce, and / or the noble metal element is Ir.

[0036] The preparation method of the catalyst provided by the present invention is simple, the synthesis conditions are simple and mild, the raw materials are easily available, and the noble metals are highly dispersed, thereby further improving the catalytic performance and stability of the catalyst. Moreover, the method of the present invention has no by-products and pollution, and can significantly save the synthesis cost and raw material cost. The application process of the CO-SCR catalyst of the present invention is simple, and can achieve the purpose of efficiently removing CO and NOx in harmful gases at a relatively high oxygen concentration.

[0037] In order to better illustrate the preparation method and beneficial effects of the catalyst, the present application specifically provides the following examples and comparative examples: Example 1

[0038] The CO-SCR catalyst Ir / Si5CeOx is prepared. The preparation method of the CO-SCR catalyst Ir / Si5CeOx is as follows: 5mmol of citric acid was dissolved in a mixed solution of 4ml of deionized water and 7ml of ethanol. Ce(NO3)3·6H2O and Si(OC2H5)4 were added to the mixed solution at a molar ratio of Si:Ce = 5:1, with a total cation molar number of 30mmol. The mixture was stirred magnetically until completely dissolved. Then 2g of polyethylene glycol was added and stirred until completely dissolved. The mixture was stirred magnetically at 80℃ until a gel was formed. The mixture was dried at 100℃ for 12h and then air calcined at 550℃ for 1h to obtain pale yellow Si5CeOx. 1g of the prepared Si5CeOx carrier was dissolved in 50ml of deionized water, stirred magnetically for 30min to ensure dispersion, and 18.345ml of IrCl3·3H2O aqueous solution was added for water bath immersion loading. After magnetic stirring at room temperature for 2h, the mixture was heated to 80℃ with stirring until the water was completely evaporated. Then it was placed in an oven for drying (100 ℃, 12 h), and then calcined in air in a tubular furnace (550 ℃, 1 h) to obtain the target CO-SCR catalyst Ir / Si5CeOx.

[0039] In the CO-SCR catalyst prepared in this example, the mass fraction of the noble metal active component Ir is 1%. Example 2

[0040] The CO-SCR catalyst Ir / Si2CeOx is prepared. The preparation method of the CO-SCR catalyst Ir / Si2CeOx is as follows: Different from Example 1, 10mmol of citric acid was dissolved in a mixed solution of 4ml of deionized water and 7ml of ethanol, Ce(NO3)3·6H2O and Si(OC2H5)4 were added to the mixed solution according to the molar ratio of Si:Ce = 2:1, with a total cation molar number of 30mmol, and magnetic stirring was performed until completely dissolved; then 2g of polyethylene glycol was added and stirred until completely dissolved, and magnetic stirring was performed at 80°C until a gel was formed; dried at 100°C for 12 h, and then air calcined at 550°C for 1 h to obtain light yellow Si2CeOx. 1g of the prepared Si2CeOx carrier was dissolved in 50ml of deionized water, magnetic stirring was performed for 30min to ensure dispersion, 18.345ml of IrCl3·3H2O aqueous solution was added for water bath immersion loading, magnetic stirring was performed for 2h, and the temperature was raised to 80°C under stirring until the water was completely evaporated. Then it was placed in an oven for drying (100 ℃, 12 h), and then calcined in air in a tubular furnace (550 ℃, 1 h) to obtain the target CO-SCR catalyst Ir / Si2CeOx.

[0041] In the CO-SCR catalyst prepared in this example, the mass fraction of the noble metal active component Ir is 1%. Example 3

[0042] The CO-SCR catalyst Ir / SiCeOx is prepared. The preparation method of the CO-SCR catalyst Ir / SiCeOx is as follows: Different from Example 1, 15mmol of citric acid was dissolved in a mixed solution of 4ml of deionized water and 7ml of ethanol, Ce(NO3)3·6H2O and Si(OC2H5)4 were added to the mixed solution according to the molar ratio of Si:Ce = 1:1, with a total cation molar number of 30mmol, and magnetic stirring was performed until completely dissolved; then 2g of polyethylene glycol was added and stirred until completely dissolved, and magnetic stirring was performed at 80°C until a gel was formed; dried at 100°C for 12 h, and then air calcined at 550°C for 1 h to obtain light yellow SiCeOx. 1g of the prepared SiCeOx carrier was dissolved in 50ml of deionized water, magnetic stirring was performed for 30min to ensure dispersion, 18.345ml of IrCl3·3H2O aqueous solution was added for water bath immersion loading, magnetic stirring was performed for 2h, and the temperature was raised to 80°C under stirring until the water was completely evaporated. Then it was placed in an oven for drying (100 ℃, 12 h), and then calcined in air in a tubular furnace (550 ℃, 1 h) to obtain the target CO-SCR catalyst Ir / SiCeOx.

[0043] In the CO-SCR catalyst prepared in this example, the mass fraction of the noble metal active component Ir is 1%. Example 4

[0044] The CO-SCR catalyst Ir / SiCe2Ox is prepared. The preparation method of the CO-SCR catalyst Ir / SiCe2Ox is as follows: Different from Example 1, 20mmol of citric acid was dissolved in a mixed solution of 4ml of deionized water and 7ml of ethanol, Ce(NO3)3·6H2O and Si(OC2H5)4 were added to the mixed solution according to the molar ratio of Si:Ce = 1:2, with a total cation molar number of 30mmol, and magnetic stirring was performed until completely dissolved; then 2g of polyethylene glycol was added and stirred until completely dissolved, and magnetic stirring was performed at 80°C until a gel was formed; dried at 100°C for 12 h, and then air calcined at 550°C for 1 h to obtain light yellow SiCe2Ox. 1g of the prepared SiCe2Ox carrier was dissolved in 50ml of deionized water, magnetic stirring was performed for 30min to ensure dispersion, 18.345ml of IrCl3·3H2O aqueous solution was added for water bath immersion loading, magnetic stirring was performed for 2h, and the temperature was raised to 80°C under stirring until the water was completely evaporated. Then it was placed in an oven for drying (100 ℃, 12 h), and then calcined in air in a tubular furnace (550 ℃, 1 h) to obtain the target CO-SCR catalyst Ir / Si1Ce2Ox.

[0045] In the CO-SCR catalyst prepared in this example, the mass fraction of the noble metal active component Ir is 1%. Example 5

[0046] The CO-SCR catalyst Ir / SiCe5Ox is prepared. The preparation method of the CO-SCR catalyst Ir / Si1Ce5Ox is as follows: Different from Example 1, 25mmol of citric acid was dissolved in a mixed solution of 4ml of deionized water and 7ml of ethanol, Ce(NO3)3·6H2O and Si(OC2H5)4 were added to the mixed solution according to the molar ratio of Si:Ce = 1:5, with a total cation molar number of 30mmol, and magnetic stirring was performed until completely dissolved; then 2g of polyethylene glycol was added and stirred until completely dissolved, and magnetic stirring was performed at 80°C until a gel was formed; dried at 100°C for 12 h, and then air calcined at 550°C for 1 h to obtain light yellow SiCe5Ox. 1g of the prepared SiCe5Ox carrier was dissolved in 50ml of deionized water, magnetic stirring was performed for 30min to ensure dispersion, 18.345ml of IrCl3·3H2O aqueous solution was added for water bath immersion loading, magnetic stirring was performed for 2h, and the temperature was raised to 80°C under stirring until the water was completely evaporated. Then it was placed in an oven for drying (100 ℃, 12 h), and then calcined in air in a tubular furnace (550 ℃, 1 h) to obtain the target CO-SCR catalyst Ir / SiCe5Ox.

[0047] In the CO-SCR catalyst prepared in this example, the mass fraction of the noble metal active component Ir is 1%.

[0048] Performance Test: The catalysts prepared in Examples 1 to 5 were used to conduct a denitrification activity test on a simulated atmosphere. The simulated flue gas contained 5000ppm CO, 500ppm NO, 1% O2, and N2 as the balance gas. 0.5ml of the above CO-SCR catalyst was placed in a quartz tube to test the catalytic activity. The concentrations of CO and NO in the outlet gas were measured every 30 minutes using a flue gas analyzer, and the removal rates of the two pollutants were calculated. The catalytic activity of the CO-SCR catalyst was evaluated by the removal rates of CO and NO.

[0049] The test results are shown in the following table:

[0050] The above table shows the NO and CO conversion rates of catalysts prepared with different Si and Ce ratios. Ir / Si2CeOx prepared with Si:Ce=2:1 has the best catalytic activity, with NO conversion rate and CO conversion rate reaching 97% and 100% at 250°C, respectively.

[0051] Ce is the capture site of Ir. If the amount of Ce added is too large, the distribution of Ce in the carrier will be uneven, which will cause Ir to aggregate and stack. The strong oxidizing property may cause excessive active oxygen to be distributed on the surface, causing Ir to be oxidized and deactivated. If the amount of Ce added is too small, the capture sites of Ir will be reduced, and some active sites will fall off during the impregnation and calcination process. The reduction of active sites will lead to a decrease in activity. Example 6

[0052] The CO-SCR catalyst Ir / Si2LaOx is prepared. The preparation method of the CO-SCR catalyst Ir / Si2LaOx is as follows: Dissolve 10mmol of citric acid in a mixed solution of 4ml of deionized water and 7ml of ethanol. Add La(NO3)3·6H2O and Si(OC2H5)4 to the mixed solution in a molar ratio of Si:La = 2:1, with a total cation molar number of 30mmol. Stir magnetically until completely dissolved. Then add 2g of polyethylene glycol and stir until completely dissolved. Stir magnetically at 80℃ until gel is formed. Dry at 100℃ for 12h, and then calcine in air at 550℃ for 1h to obtain white Si2La1Ox. Take 1g of the prepared Si2LaOx carrier and dissolve it in 50ml of deionized water. Stir magnetically for 30min to ensure dispersion. Add 18.345ml of IrCl3·3H2O aqueous solution for water bath immersion loading. Stir magnetically for 2h, and heat to 80℃ with stirring until the water is completely evaporated. Then it was placed in an oven for drying (100 ℃, 12 h), and then calcined in air in a tubular furnace (550 ℃, 1 h) to obtain the target CO-SCR catalyst Ir / Si2LaOx.

[0053] In the CO-SCR catalyst prepared in this example, the mass fraction of the noble metal active component Ir is 1%. Example 7

[0054] The CO-SCR catalyst Ir / Si2PrOx is prepared. The preparation method of the CO-SCR catalyst Ir / Si2PrOx is as follows: 10mmol of citric acid was dissolved in a mixed solution of 4ml of deionized water and 7ml of ethanol. Pr(NO3)3·6H2O and Si(OC2H5)4 were added to the mixed solution according to the molar ratio of Si:Pr=2:1, with a total cation molar number of 30mmol. The mixture was stirred magnetically until completely dissolved. Then 2g of polyethylene glycol was added and stirred until completely dissolved. The mixture was stirred magnetically at 80℃ until a gel was formed. The mixture was dried at 100℃ for 12h and then calcined in air at 550℃ for 1h to obtain light green Si2PrOx. 1g of the prepared Si2PrOx carrier was dissolved in 50ml of deionized water, stirred magnetically for 30min to ensure dispersion, and 18.345ml of IrCl3·3H2O aqueous solution was added for water bath impregnation loading. After magnetic stirring for 2h, the mixture was heated to 80℃ with stirring until the water was completely evaporated. Then it was placed in an oven for drying (100 ℃, 12 h), and then calcined in air in a tubular furnace (550 ℃, 1 h) to obtain the target CO-SCR catalyst Ir / Si2PrOx.

[0055] In the CO-SCR catalyst prepared in this example, the mass fraction of the noble metal active component Ir is 1%. Example 8

[0056] The CO-SCR catalyst Ir / Si2ZrOx is prepared. The preparation method of the CO-SCR catalyst Ir / Si2ZrOx is as follows: 10mmol of citric acid was dissolved in a mixed solution of 4ml of deionized water and 7ml of ethanol. ZrO(NO3)2·xH2O and Si(OC2H5)4 were added to the mixed solution according to the molar ratio of Si:Zr=2:1, with a total cation molar number of 30mmol. The mixture was stirred magnetically until completely dissolved. Then 2g of polyethylene glycol was added and stirred until completely dissolved. The mixture was stirred magnetically at 80℃ until a gel was formed. The mixture was dried at 100℃ for 12h and then air calcined at 550℃ for 1h to obtain white Si2ZrOx. 1g of the prepared Si2ZrOx carrier was dissolved in 50ml of deionized water, stirred magnetically for 30min to ensure dispersion, and 18.345ml of IrCl3·3H2O aqueous solution was added for water bath impregnation loading. After magnetic stirring for 2h, the mixture was heated to 80℃ with stirring until the water was completely evaporated. Then it was placed in an oven for drying (100 ℃, 12 h), and then calcined in air in a tubular furnace (550 ℃, 1 h) to obtain the target CO-SCR catalyst Ir / Si2ZrOx.

[0057] In the CO-SCR catalyst prepared in this example, the mass fraction of the noble metal active component Ir is 1%.

[0058] Performance Test: The catalysts prepared in Examples 6 to 8 above were used to conduct a denitrification activity test on a simulated atmosphere. The simulated flue gas contained 5000ppm CO, 500ppm NO, 1% O2, and N2 as the balance gas. 0.5ml of the above CO-SCR catalyst was placed in a quartz tube to test the catalytic activity. The concentrations of CO and NO in the outlet gas were measured every 30 minutes using a flue gas analyzer, and the removal rates of the two pollutants were calculated. The catalytic activity of the CO-SCR catalyst was evaluated by the removal rates of CO and NO.

[0059] The test results are shown in the following table:

[0060] The above table shows the NO and CO conversion rates of catalysts prepared with different rare earth metals as added elements. Compared with Example 2, it can be seen that Ir / SiCeOx prepared by selecting Ce as the added element has the best catalytic activity, and the NO conversion rate and CO conversion rate reach 97% and 100% at 250°C, respectively.

[0061] Due to its oxygen storage capacity and strong interaction with Ir, Ce can provide electrons to Ir, putting Ir in a reduced state, thereby improving its antioxidant capacity and catalytic activity. Example 9

[0062] The CO-SCR catalyst Ir / Si2CeOx with a precious metal content of 0.1wt% was prepared by the following method: Different from Example 1, after preparing the Si2CeOx carrier, 1g of the carrier was dissolved in deionized water, and 1.8345ml of IrCl3·3H2O with a concentration of 1㎎ / ml was added for water bath impregnation loading. After magnetic stirring for 2h, the temperature was raised to 80℃ under stirring until the water was completely evaporated. Then, it was placed in an oven for drying (100℃, 12h), and then calcined in air in a tubular furnace (550℃, 1h) to obtain the target CO-SCR catalyst Ir / Si2CeOx.

[0063] In the CO-SCR catalyst prepared in this example, the mass fraction of the precious metal active component Ir is 0.1%.

[0064] Example 10 The CO-SCR catalyst Ir / Si2CeOx with a precious metal content of 0.5wt% was prepared by the following method: Different from Example 1, after preparing the Si2CeOx carrier, 1g of the carrier was dissolved in deionized water, and 9.1725ml of IrCl3·3H2O solution with a concentration of 1㎎ / ml was added for water bath impregnation loading, and the temperature was raised to 80°C under magnetic stirring for 2h until the water was completely evaporated. Then it was placed in an oven for drying (100°C, 12h), and then calcined in air in a tubular furnace (550°C, 1h) to obtain the target CO-SCR catalyst Ir / Si2CeOx.

[0065] In the CO-SCR catalyst prepared in this example, the mass fraction of the noble metal active component Ir is 0.5%.

[0066] Embodiment 11 The CO-SCR catalyst Ir / Si2CeOx with a precious metal content of 2 wt% was prepared by the following method: Different from Example 1, after preparing the Si2CeOx carrier, 1g of the carrier was dissolved in deionized water, and 36.69ml of IrCl3·3H2O solution with a concentration of 1㎎ / ml was added for water bath impregnation loading. After magnetic stirring for 2h, the temperature was raised to 80℃ under stirring until the water was completely evaporated. Then, it was placed in an oven for drying (100℃, 12h), and then calcined in air in a tubular furnace (550℃, 1h) to obtain the target CO-SCR catalyst Ir / Si2CeOx.

[0067] In the CO-SCR catalyst prepared in this example, the mass fraction of the precious metal active component Ir is 2%.

[0068] Example 12 The CO-SCR catalyst Ir / Si2CeOx with a precious metal content of 5 wt% was prepared by the following method: Different from Example 1, after preparing the Si2CeOx carrier, 1g of the carrier was dissolved in deionized water, and 91.725ml of IrCl3·3H2O solution with a concentration of 1㎎ / ml was added for water bath impregnation loading. After magnetic stirring for 2h, the temperature was raised to 80℃ under stirring until the water was completely evaporated. Then, it was placed in an oven for drying (100℃, 12h), and then calcined in air in a tubular furnace (550℃, 1h) to obtain the target CO-SCR catalyst Ir / Si2CeOx.

[0069] In the CO-SCR catalyst prepared in this embodiment, the mass fraction of the precious metal active component Ir is 5%; Performance Test: The catalysts prepared in Examples 9 to 11 were used to conduct a denitrification activity test in a simulated atmosphere. The simulated flue gas contained 5000ppm CO, 500ppm NO, 1% O2, and N2 as the balance gas. 0.5ml of the above CO-SCR catalyst was placed in a quartz tube to test the catalytic activity. The concentrations of CO and NO in the outlet gas were measured every 30 minutes using a flue gas analyzer, and the removal rates of the two pollutants were calculated. The catalytic activity of the CO-SCR catalyst was evaluated by the removal rates of CO and NO.

[0070] The test results are shown in the following table:

[0071] The above table shows the NO and CO conversion rates of catalysts prepared with different Ir loading amounts. From this table, it can be seen that 1wt% Ir / Si2CeOx prepared with an Ir loading of 1wt% in Example 2 has the best catalytic activity, and the NOx conversion rate and CO conversion rate reach 97% and 100% at 250°C, respectively.

[0072] Too low a loading amount will result in insufficient active components. Although too high a loading amount will improve the activity, from an economic point of view, 1wt% IrCl3·3H2O is the best dosage.

[0073] Comparative Example 1 The CO-SCR catalyst Ir / SiO2 was prepared in a similar manner to that in Example 2, except that the added precursors were different. The steps were as follows: 5mmol of citric acid was dissolved in a mixed solution of 4ml of deionized water and 7ml of ethanol, Si(OC2H5)4 was added to the mixed solution with a total cation molar number of 30mmol, and magnetic stirring was performed until it was completely dissolved; then 2g of polyethylene glycol was added and stirred until it was completely dissolved, and magnetic stirring was performed at 80℃ until a gel was formed; it was dried at 100℃ for 12h, and then air calcined at 550℃ for 1h to obtain a white SiO2 carrier. 1g of the prepared SiO2 carrier was dissolved in 50ml of deionized water, magnetic stirring was performed for 30min to ensure dispersion, and 18.345ml of IrCl3·3H2O aqueous solution was added for water bath impregnation loading, magnetic stirring was performed for 2h, and the temperature was raised to 80℃ under stirring until the water was completely evaporated. It was then placed in an oven for drying (100℃, 12h), and then air calcined in a tubular furnace (550℃, 1h) to obtain the target CO-SCR catalyst Ir / SiO2.

[0074] Comparative Example 2 The CO-SCR catalyst Ir / CeO2 was prepared in a similar manner to that in Example 2, except that the added precursors were different. The steps were as follows: 30mmol of citric acid was dissolved in a mixed solution of 4ml of deionized water and 7ml of ethanol, Ce(NO3)3·6H2O was added to the mixed solution with a total cation mole of 30mmol, and magnetic stirring was performed until it was completely dissolved; then 2g of polyethylene glycol was added and stirred until it was completely dissolved, and magnetic stirring was performed at 80℃ until a gel was formed; it was dried at 100℃ for 12h, and then air calcined at 550℃ for 1h to obtain a light yellow CeO2 carrier. 1g of the prepared CeO2 carrier was dissolved in 50ml of deionized water, magnetic stirring was performed for 30min to ensure dispersion, and 18.345ml of IrCl3·3H2O aqueous solution was added for water bath immersion loading, magnetic stirring was performed for 2h, and the temperature was raised to 80℃ under stirring until the water was completely evaporated. Then it was placed in an oven for drying (100 ℃, 12 h), and then calcined in air in a tubular furnace (550 ℃, 1 h) to obtain the target CO-SCR catalyst Ir / CeO2.

[0075] Performance Test: The catalysts prepared in Comparative Examples 1 and 2 were used to conduct a denitrification activity test in a simulated atmosphere. The simulated flue gas contained 5000ppm CO, 500ppm NO, 1% O2, and N2 as the balance gas. 0.5ml of the above CO-SCR catalyst was placed in a quartz tube to test the catalytic activity. The concentrations of CO and NO in the outlet gas were measured every 30 minutes using a flue gas analyzer, and the removal rates of the two pollutants were calculated. The catalytic activity of the CO-SCR catalyst was evaluated by the removal rates of CO and NO.

[0076] The test results are shown in the following table:

[0077] The above table shows the NO and CO conversion rates of the three catalysts Ir / Si2CeOx, Ir / SiO2, and Ir / CeO2. Ir / Si2CeOx has the best catalytic activity, with NO conversion rate and CO conversion rate reaching 97% and 100% at 250°C, respectively.

[0078] By comparing the three catalysts, the roles of Si and Ce are further proposed. Silicon plays the role of dispersing cerium in the carrier, and cerium, as a capture site for precious metal Ir, plays the role of dispersing Ir. More importantly, it has a strong interaction with Ir, keeping Ir in a reduced state.

[0079] Figure 2 This is the long-term stability test chart of Ir / Si2CeOx catalyst. Within 30 hours, the NO conversion rate dropped by less than 10%, and the CO conversion rate remained almost unchanged, which shows that the Ir / Si2CeOx catalyst has good stability.

[0080] In a third aspect, the present invention further provides a reactor, comprising a catalyst for promoting a chemical reaction between nitrogen oxides and carbon monoxide, wherein the catalyst is any of the catalysts provided in the embodiments of the present application.

[0081] The present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A catalyst in which a noble metal element is supported on an oxide carrier, characterized in that: The catalyst comprises an oxide support and a precious metal element loaded on the oxide support, wherein the precious metal element is selected from at least one element of Au, Ag, Ru, Rh, Pd, Os, Ir, and Pt, and the general formula of the oxide support is SiMOx, wherein M is an additive element, and the additive element M is selected from at least one element of Ce, La, Pr, and Zr, and x is the number of O atoms required to satisfy the valence balance of the general formula.

2. The catalyst according to claim 1, characterized in that The noble metal element is Ir, the additional element M is Ce, and the oxide carrier is a mixed oxide containing SiO2 and CeO2.

3. A method for preparing a catalyst in which a noble metal element is supported on an oxide carrier, characterized in that: The following steps are involved: Step S1, dissolving citric acid in a mixed solution of deionized water and ethanol, adding an additive element M precursor and a Si precursor, stirring until completely dissolved, then adding polyethylene glycol, heating and stirring to obtain a gel, wherein the additive element M is at least one element selected from Ce, La, Pr, and Zr; Step S2, drying the gel and then calcining it in air to obtain an intermediate; Step S3, dispersing the intermediate in deionized water, adding an aqueous solution containing a precious metal element, heating and stirring until evaporated to dryness, drying, and air calcining to obtain a catalyst in which the precious metal element is supported on an oxide carrier, wherein the precious metal element is selected from at least one element of Au, Ag, Ru, Rh, Pd, Os, Ir, and Pt.

4. The method for preparing a catalyst according to claim 3, characterized in that: In the step S1, the ratio of the sum of the moles of the additive element M precursor and the Si precursor, the moles of polyethylene glycol, the moles of deionized water, and the moles of ethanol is 30:0.3:222:

121.

5. The method for preparing a catalyst according to claim 3, characterized in that: In the step S1, the molar ratio of citric acid to the precursor of the additive element M is 1:

1.

6. The method for preparing a catalyst according to claim 3, characterized in that: In the step S1, the molar ratio of the Si precursor to the additive element M precursor is 1:(0.2-5).

7. The method for preparing a catalyst according to claim 3, characterized in that: In step S3, the mass ratio of the intermediate to deionized water is 1:50; the mass ratio of the noble metal element in the aqueous solution containing the noble metal element to the intermediate is 0.1%-5%, and the concentration of the aqueous solution containing the noble metal element is 1 mg / ml.

8. The method for preparing a catalyst according to claim 3, characterized in that: In the step S1, the temperature of heating and stirring is 80°C; and / or In the step S2, the drying temperature of the gel is 100°C and the drying time is 12 hours; the air calcination temperature of the gel is 550°C and the air calcination time is 1 hour; and / or In the step S3, the heating and stirring time is 2 hours, the heating and stirring temperature is 80°C; the drying temperature is 100°C; the air calcination temperature is 550°C, and the air calcination time is 1 hour.

9. The method for preparing a catalyst according to claim 3, characterized in that: The additional element M is Ce, and / or the noble metal element is Ir.

10. A reactor, characterized in that: The reactor contains a catalyst for promoting a chemical reaction between nitrogen oxides and carbon monoxide, wherein the catalyst is the catalyst according to any one of claims 1-9.

Citation Information

Patent Citations

  • CO-SCR denitration catalyst as well as preparation method and application thereof

    CN113275008A

  • CO-SCR catalyst and preparation method and application thereof

    CN117884121A